Decision Support System for Determining the Best Employee with Web-Based AHP Method at Pariwisata Polytechnic - Syahputra, Ilham; Ruziq, Fahmi; Rambe, Aripin (Journal of Technology and Computer, 2024)
A Decision Support System (DSS) for Best Employee Determination Selection using the Analytical Hierarchy Process (AHP) method is an essential tool for enhancing employee performance and motivation. The awards given by companies to their best employees serve as a powerful incentive, driving each employee to consistently deliver their best work. To determine the best employee, companies assess performance over a specific period, considering various criteria. At Medan Tourism Polytechnic, these criteria include work behavior, work discipline, honesty, loyalty, and cooperation. The AHP method structures the decision-making process into a hierarchical model, allowing for systematic evaluation of alternative choices against the set criteria. By assigning weights to each criterion, AHP quantifies subjective assessments, providing an objective basis for comparing employees. This method ensures transparency and fairness in the selection process, promoting a culture of excellence and motivation among employees. Implementing a DSS with the AHP method not only simplifies the evaluation process but also ensures that decisions are based on measurable performance indicators. This fosters an environment where employees are encouraged to continuously improve their performance, contributing to the overall productivity and success of the organization. This system is integral in maintaining high standards and employee satisfaction within the organization.